2003
DOI: 10.1073/pnas.1932826100
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells can form germ cells in vitro

Abstract: Knock-in embryonic stem (ES) cells, in which GFP or lacZ was expressed from the endogenous mouse vasa homolog (Mvh), which is specifically expressed in differentiating germ cells, were used to visualize germ cell production during in vitro differentiation. The appearance of MVH-positive germ cells depended on embryoid body formation and was greatly enhanced by the inductive effects of bone morphogenic protein 4-producing cells. The ES-derived MVH-positive cells could participate in spermatogenesis when transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
534
4
27

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(576 citation statements)
references
References 30 publications
11
534
4
27
Order By: Relevance
“…In this regard, germ cells or primordial germ cells reported or claimed to have been derived from ES/iPS cells and epiblast cells [34][35][36][37] could be tested regarding their spermatogenic activity with our in vitro system. This particular application of our method would break the boundary between germ and somatic cells, and open a new phase in germ cell research.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, germ cells or primordial germ cells reported or claimed to have been derived from ES/iPS cells and epiblast cells [34][35][36][37] could be tested regarding their spermatogenic activity with our in vitro system. This particular application of our method would break the boundary between germ and somatic cells, and open a new phase in germ cell research.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of differentiation from ES or iPS cells into haploid male germ cells is generally reported to be low. [14][15][16][17][18][19][20][21][22][23][24] Although there is no evidence for the speculation that this efficiency might be higher using AFS cells, to our opinion, the here reviewed knowledge warrants testing this new stem cell type for their usability for the in vitro investigation of sperm production (Figure 1).…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 89%
“…Since spontaneous induction of meiosis is low, overexpression of genes of the DAZ gene family can be performed to induce meiosis for haploid spermatids 5,27 ( Figure 1). Finally, in mice it is possible to test the biological function of so-obtained haploid male gametes either by transplantation into busulfan-mediated sperm-depleted testes to check in vivo differentiation, or by intracytoplasmic injection into recipient oocytes to test whether this supports cleavage [14][15][16] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Toyooka and colleagues 53 have reported finding mature germ cells from their cultured ESCs injected into a mouse testis. In a landmark paper, Geijsen et al 54 reported the derivation of mouse PGCs by adding retinoic acid to an ESC culture media.…”
Section: From Embryonic Stem Cells To Germ Cellsmentioning
confidence: 99%